Long non-coding RNAs and JAK/STAT signaling pathway regulation in colorectal cancer development - Ghasemian, Abdolmajid; Omear, Hadeel A.; Mansoori, Yaser; Mansouri, Pardis; Deng, Xinpei; Darbeheshti, Farzaneh; Zarenezhad, Elham; Kohansal, Maryam; Pezeshki, Babak; Wang, Zhangling; Tang, Hailin (Frontiers in Genetics, 2023)
Colorectal cancer (CRC) is among main fatal cancers. Cell signaling such as Janus kinase signal transducer and activator of transcription (JAK/STAT) signaling substantially influences the process of the gene expression and cell growth. Long non-coding RNAs have regulatory roles in the cell signaling, cell proliferation and cancer fate. Hence, lncRNAs can be considered as biomarkers in cancers. The inhibitory or activating effects of different lncRNAs on the JAK/STAT pathway regulate cancer cell proliferation or tumor suppression. Additionally, lncRNAs regulate immune responses which have a role in immunotherapy. Mechanisms of lncRNAs in the CRC via the JAK/STAT regulation mainly include cell proliferation, invasion, metastasis, apoptosis, adhesion, and control of inflammation. More profound findings are warranted to specifically target the lncRNAs in terms of activation or suppression in hindering CRC cells’ proliferation. Here, to understand the lncRNAs cross-talk in CRC through JAK/STAT signaling pathway, we have gathered the related in-vitro and in-vivo data. Future insights may pave the way for the development of novel diagnostic tools, therapeutic interventions, and personalized treatment strategies for CRC patients.